The Assembly of Cell-Encapsulating Microscale Hydrogels Using Acoustic Waves - Xu, Feng (2011)
Microscale hydrogels find widespread applications in medicine and biology, e.g., as building blocks for tissue engineering and regenerative medicine. In these applications, these microgels are assembled to fabricate large complex 3D constructs. The success of this approach requires non-destructive and high throughput assembly of the microgels. Although various assembly methods have been developed based on modifying interfaces, and using microfluidics, so far, none of the available assembly technologies have shown the ability to assembly microgels using non-invasive fields rapidly within seconds in an efficient way. Acoustics has been widely used in biomedical area to manipulatedroplets, cells and biomolecules. In this study, we developed a simple, non-invasiveacoustic assembler for cell-encapsulating microgels with maintained cell viability (>93%). We assessed the assembler for both microbeads (with diameter of 50 µm and 100 µm) and microgels of different sizes and shapes (e.g., cubes, lock-and-key shapes, tetris, saw) in microdroplets (with volume of 10 µL, 20 µL, 40 µL, 80 µL). The microgels were assembled in second sin a non-invasive manner. These results indicate that the developed acoustic approach could become an enabling biotechnology tool for tissue engineering, regenerative medicine, pharmacology studies and high throughput screening applications.